Attitudes to fertility issues among adults with cystic fibrosis in Scotland. Issue 8 (1st August 2000) - Fair, A; Griffiths, K; Osman, L M
Abstract : BACKGROUND: With increasing life expectancy, issues of fertility and pregnancy are pertinent to patients with cystic fibrosis. For this reason, the four Scottish Cystic Fibrosis centres asked men and women with cystic fibrosis about their attitudes to fertility and to information given to them by health professionals. METHODS: A postal questionnaire was sent to 116 men and 79 women aged 16 years and over attending four Scottish Cystic Fibrosis clinics. RESULTS: There was a 70% response rate (82 men, 54 women). All but two men knew that they were likely to be infertile. 37% of respondents lived with a partner; 14 women (26%) and five men (6%) had children. For 85% of men and 72% of women having children was important now or would be in the next 10 years. 43% of men and 26% of women had never had any discussion on fertility issues with cystic fibrosis health professionals. 56% of men thought that first discussion with a health professional about infertility should be before the age of 16 years; 12% remembered having a first discussion at that age. Learning of their infertility was associated with strong negative emotions for most men. Women were more likely than men to have initiated first discussion (17 (32%) versus eight (10%); p<0.01). Twenty five men (31%) and 32 women (59%) were currently using contraception. Ten men (12%) and 15 women (28%) had discussed contraception at the Cystic Fibrosis clinic (p = 0.01). CONCLUSIONS: Parenting and fertility issues are important for men and women with cystic fibrosis but many patients do not find out what they want to know from discussion with health professionals. Patients want discussion to begin in early adolescence. Men in particular are likely to be reluctant to introduce these issues; health professionals should be aware of the need actively to initiate discussion.